Peran Rumah Kreatif Tambak Bayan dalam Meningkatkan Literasi pada Anak-Anak di Desa Saentis - Sani Susanti; Melly Br Bangun; Rista Triwani; Cindy Nadya; Sondang Dioranta; Lidya Natasya (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2024)
Literacy is an important skill that every individual must have to function well in a social environment and face the challenges of the era of globalization. This article discusses the role of the Tambak Bayan Creative House in increasing human literacy, especially among children in Saentis Village. These creative at-home activities, such as role playing with dolls, provide positive benefits for children's development, including the development of emotional maturity, empathy, communication and problem-solving skills. Involving the community in creative work at the Tambak Bayan Creative House also provides significant benefits, such as increasing the sense of responsibility, pride and empowerment among community members. Apart from that, this activity also stimulates new interests and potential among community members. The research methods used are survey, interview, observation and documentation methods which are carried out by collecting data through questionnaires or respondent interviews. Thus, the Tambak Bayan Creative House has a significant role in increasing human literacy and community creativity, and has the potential to become an effective and inclusive learning model.